KARAKTERISTIK PENDERITA HIPERTENSI YANG DIRAWAT INAP DI RUMAH SAKIT VITA INSANI PEMATANGSIANTAR TAHUN 2010-2011 - Evi Susanti Sinaga; hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Hypertension is one of the degenerative disease a public health problem in the world because hypertension often appears without symptoms. In Indonesia, people with hypertension are estimated at 15 million but only 4% controlled hypertension. According to the Ministry of Health of the Republic of Indonesia (2010) suggested that hypertension is the third cause of death is by PMR 6,7% of the population deaths in all age groups in Indonesia. To know the characteristics of patients who are hospitalized at Vita Insani Hospital Pematangsiantar, descriptive study has been done by using case series design and continued with the statistical analysis. The population and sample were 130 data patients (total sampling). From the recorded data, the results obtained by the highest proportion of female patients in the age group >60 years (30,8%), Batak (77,7%), Protestant (64,6%), house wives (24,6%), married (66,9%), out of Pematangsiantar (59,2%), headache (71,5%), third degree of hypertension (66,2%) without comorbidity (76,9%), stroke, and diabetes mellitus (33,3%), average length of stay 3,75 days, medically discharged and becoming out patient (83,1%). There is no significant difference between the sexes with the degree of hypertension (p= 0,252). There is no significant difference in the average length of stay patients with a degree of hypertension (p = 0,922). To hypertensive patients aged> 60 years for his blood pressure checked regularly and maintain a diet and a healthy life. Communities should be empowered, through education in order to contribute effectively to the prevention and control of hypertension. Keywords: hypertension, patient characteristics, Vita Insani hospital Pematangsiantar